PELAKSANAAN DIVERSIFIKASI PRODUK DALAM RANGKA MENINGKATKAN VOLUME EKSPOR (Studi Kasus Perusahaan Batik Ayu di Kota Pekalongan) - Nurul Hidayah Indah; Suharyono Suharyono; Sunarti Sunarti (Fakultas Ilmu Administrasi Universitas Brawijaya, 2017)
The textile industry is one of the leading industries of Indonesia, both in the domestic trade and international trade. Indonesian textile products of the flagship and pride of Indonesian batik. The purpose of this study: 1) To investigate the implementation of product diversification strategy and 2) To determine the impact of product diversification strategy to increase the export volume in the Company batik Ayu. This type of research used in this study is a qualitative study using a descriptive approach. The focus of research is on the company's product diversification strategy batik Ayu and the impact of product diversification strategy.The analysis showed that the attempt was first made by the owner is doing batik training for local people, finally in 2004 the owners founded the company Batik Cap